De novo assembly of maritime pine transcriptome: implications for forest breeding and biotechnology. Issue 3 (21st November 2013) - Canales, Javier; Bautista, Rocio; Label, Philippe; Gómez‐Maldonado, Josefa; Lesur, Isabelle; Fernández‐Pozo, Noe; Rueda‐López, Marina; Guerrero‐Fernández, Dario; Castro‐Rodríguez, Vanessa; Benzekri, Hicham; Cañas, Rafael A.; Guevara, María‐Angeles; et al.
Summary Maritime pine (Pinus pinasterAit.) is a widely distributed conifer species in Southwestern Europe and one of the most advanced models for conifer research. In the current work, comprehensive characterization of the maritime pine transcriptome was performed using a combination of two different next‐generation sequencing platforms, 454 and Illumina. De novo assembly of the transcriptome provided a catalogue of 26 020 unique transcripts in maritime pine trees and a collection of 9641 full‐length cDNAs. Quality of the transcriptome assembly was validated by RT‐PCR amplification of selected transcripts for structural and regulatory genes. Transcription factors and enzyme‐encoding transcripts were annotated. Furthermore, the available sequencing data permitted the identification of polymorphisms and the establishment of robust single nucleotide polymorphism (SNP) and simple‐sequence repeat (SSR) databases for genotyping applications and integration of translational genomics in maritime pine breeding programmes. All our data are freely available at SustainpineDB, the P. pinaster expressional database. Results reported here on the maritime pine transcriptome represent a valuable resource for future basic and applied studies on this ecological and economically important pine species.